Investigasi Eksperimental Pengaruh Variasi Jenis Pelumas dan Kecepatan Putar Motor Terhadap Reduksi Diameter Kawat Titanium Murni Komersial Pada Proses Penarikan Kawat - Iqbal; Yovial Mahyoedin; Iman Satria; Agil Pebri Saputra (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2026)
Commercially pure titanium (CP-Ti) has the potential as an alternative material for orthodontic wires due to its combination of high biocompatibility, good corrosion resistance, and mechanical characteristics that support clinical applications. This study aims to analyse the effect of different types of lubricants on the mechanical properties of titanium wire processed through the wire drawing method. The drawing process was carried out using two types of lubricants, namely oil and gomok, under the same diameter reduction conditions. Material characterisation was conducted through wire drawing tests, hardness tests, and microstructure observation to evaluate the effect of lubrication on the results of plastic deformation. The research results show that the use of oil produces a more stable drawing process and better mechanical properties compared to the use of gomok. In addition, effective lubrication can reduce frictional resistance during the deformation process, resulting in better surface quality and structural homogeneity. These findings indicate that the type of lubricant is an important parameter in the titanium wire drawing process and has the potential to improve the final product quality for orthodontic applications.